2020
DOI: 10.1002/wdev.378
|View full text |Cite
|
Sign up to set email alerts
|

The Drosophila gut: A gatekeeper and coordinator of organism fitness and physiology

Abstract: Multicellular organisms have evolved organs and tissues with highly specialized tasks. For instance, nutrients are assimilated by the gut, sensed, processed, stored, and released by adipose tissues and liver to provide energy consumed by peripheral organ activities. The function of each organ is modified by local clues and systemic signals derived from other organs to ensure a coordinated response accommodating the physiological needs of the organism. The intestine, which represents one of the largest interfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 141 publications
(271 reference statements)
1
28
0
Order By: Relevance
“…Like juvenile growth, adult growth is influenced by physiological needs and environmental cues. For example, mating induces growth in the reproductive systems of both males and females, and the adult gut undergoes remodeling in response to environmental conditions, mating, and infection to maintain tissue homeostasis ( Leiblich et al 2012 , 2019 ; Ameku and Niwa 2016 ; Ameku et al 2018 ; Colombani and Andersen 2020 ). Adult tissue growth and oogenesis are governed by cell-intrinsic and systemic mechanisms similar to those of juveniles, including TOR, insulin and ecdysone, juvenile hormone (JH), cytokines, TNF-α, and transforming growth factor-β (TGF-β) ( Petryk et al 2003 ; Ono et al 2006 ; Knapp and Sun 2017 ; Colombani and Andersen 2020 ).…”
Section: Regulation Of Cell Size and Numbermentioning
confidence: 99%
“…Like juvenile growth, adult growth is influenced by physiological needs and environmental cues. For example, mating induces growth in the reproductive systems of both males and females, and the adult gut undergoes remodeling in response to environmental conditions, mating, and infection to maintain tissue homeostasis ( Leiblich et al 2012 , 2019 ; Ameku and Niwa 2016 ; Ameku et al 2018 ; Colombani and Andersen 2020 ). Adult tissue growth and oogenesis are governed by cell-intrinsic and systemic mechanisms similar to those of juveniles, including TOR, insulin and ecdysone, juvenile hormone (JH), cytokines, TNF-α, and transforming growth factor-β (TGF-β) ( Petryk et al 2003 ; Ono et al 2006 ; Knapp and Sun 2017 ; Colombani and Andersen 2020 ).…”
Section: Regulation Of Cell Size and Numbermentioning
confidence: 99%
“…Furthermore, microbes also interact with insect host to modulate adult oviposition behaviour (Jose et al 2019), foraging (Wong et al 2017), reproductive success (Morimoto et al 2017b) and potentially mate choice (Sharon et al 2011) [but see (Leftwich et al 2017)]. Microbes are therefore the 'gatekeepers of organism fitness' (Colombani and Andersen 2020).…”
Section: Interactions Between Host and Microbesmentioning
confidence: 99%
“…The gut has emerged as a central signal-integrating regulator of whole-body energy homeostasis. Despite the evolutionary divergence of flies and humans, the guts of these animals exhibit physiological and structural similarity, with the Drosophila midgut functioning analogously to the human small intestine 6,7 . Work in mammals and Drosophila has shown that the gut integrates nutritional and microbiotic cues and converts these into hormonal signals that relay nutritional information systemically to other tissues.…”
Section: Gut-derived Astc Regulates Metabolism and Food Intake To Maimentioning
confidence: 99%